Cultural appropriation and the arts - Young, James O., 1957- (Malden (Mass) : Wiley-Blackwell, 2010)
Now, for the first time, a philosopher undertakes a systematic investigation of the moral and aesthetic issues to which cultural appropriation gives rise. Cultural appropriation is a pervasive feature of the contemporary world (the Parthenon Marbles remain in London; white musicians from Bix Beiderbeck to Eric Clapton have appropriated musical styles from African-American culture) Young offers the first systematic philosophical investigation of the moral and aesthetic issues to which cultural appropriation gives rise Tackles head on the thorny issues arising from the clash and integration of cultures and their artifacts Questions considered include: & Can cultural appropriation result in the production of aesthetically successful works of art?& and & Is cultural appropriation in the arts morally objectionable?& Part of the highly regarded New Directions in Aesthetics series
What is cultural appropriation? -- The aesthetics of cultural appropriation -- Cultural appropriation as theft -- Cultural appropriation as assault -- Profound offence and cultural appropriation -- Conclusion: responding to cultural appropriation.
boek
Keywords: Arts and society; Arts -- Moral and ethical aspects; Cultural property